Any use for alternative lock solutions in the prevention of catheter-related blood stream infections?. Issue 1 (March 2017) - Labriola, Laura; Pochet, Jean-Michel
The prevention of catheter-related blood stream infections (CRBSI) in hemodialysis (HD) patients remains a challenge because of high morbidity and mortality associated to CRBSI. Alternative locking solutions (ALS) containing an antithrombotic substance with additional antimicrobial or antibiofilm properties (citrate, ethylenediaminetetraacetic acid [EDTA], 70% ethanol, thrombolytics) with or without the addition of molecules with specific antimicrobial activity (antibiotics, taurolidine, paraben-methylene-blue) has been proposed with the aim to prevent or eradicate intraluminal biofilm colonization and subsequent CRBSI. In this review, we examine the available evidence concerning their efficacy and potential side effects, in order to determine whether ALS should be implemented widely or only in selected cases.